Effect Analysis of Track Vibration Reduction Measures on Viaduct Environmental Vibration Induced by Vehicle Operation - YANG Lin; FANG Bin; NIU Xiaoli; YUAN Dehao (Chengshi guidao jiaotong yanjiu, 2024)
［Objective］When a train running on the viaduct track, the rail vibration caused by the vehicle-track interaction will be transmitted to the bridge, piers, and pile foundations through the track structure, thereby triggering ground vibration around the bridge. Therefore, it is necessary to study the impact of elevated section rail and track bed vibration reduction on the environment for elevated rail transit. ［Method］Based on the vehicle-track multi-body dynamics theory and the finite element method, a vehicle-track-U beam bridge-soil vibration model is established to solve the vibration response of the ground source intensity near the viaduct when rail transit veh-icles passing through. ［Result & Conclusion］The peak frequency band of the ground source intensity vertical vibration frequency for elevated section is distributed in 40 ~ 60 Hz. Vibration-damping fasteners, trapezoidal sleepers, vibration-damping pad floating plates and steel spring floating plates all have a reduction effect on the ground source intensity vibration, and their contribution is mainly reflected in the vibration frequency range of 25 ~ 100 Hz. Under the conditions of using vibration-damping fasteners, trapezoidal sleepers, vibration-damping pad floating plates, and steel spring floating plates, when the vibration frequency is 40 ~ 50 Hz, the ground source intensity vibration acceleration levels are reduced by about 4.2 ~ 4.4 dB, 6.5 ~ 6.9 dB, 7.8 ~ 8.1 dB and 10.0~10.7 dB respectively. When the fastener stiffness is ≤15 kN/mm, the rail vertical displacement and vertical acceleration peak value increase significantly. When the fastener stiffness decreases from 60 kN/mm to 10 kN/mm, the rail vertical displacement and acceleration peak value increase by about 5 times and 18.26% respectively. In the peak frequency band of 40 ~ 50 Hz, the vertical vibration acceleration level at the ground source intensity decreases by about 4.5 ~ 4.9 dB.